The Problems Facing Students of English with Learning Disabilities from their Teachers' Point of View - Khasawneh, Mohamad Ahmad Saleem (Universitas Negeri Semarang, 2020)
Students with learning disabilities face different problems while studying English language. This group of students have special features that are different from their regular peers. Therefore, there is a need to identify these challenges and problems to help educators deal with this issue. This study aimed at identifying and evaluating the problems facing English language students with learning disabilities from their teachers ’point of view in Bani Ubaid district in the Hashemite Kingdom of Jordan. The study population consisted of all (170) English language teachers. The sample was chosen randomly at a rate of (50 %) of the teachers, and their number was (85). The study used the survey approach and developed a questionnaire consisting of (30) paragraphs distributed into (3) areas: the academic field, the administrative field, and the social field. The results of the study showed that the problems facing English language students with learning disabilities from the teachers' point of view were arranged according to the different fields of importance as follows: social, health, and administrative.